Diversity, ecology, and electrogenic mechanism of electrochemically active bacteria - Yanyu Xiao; Shicheng Wang; Shuang Zhang; Xinxin Fan; Yating Wang; Lei Yan (Biomass and Bioenergy, 2027)

Climate change, water quality, and water diversion are associated with the shifts of aquatic vegetation structure and phenology in five temperate regulating lakes of eastern China - Yan Guo; Shilong Ren; Quanzhou Yu; Xiaohui Bai; Shuping Ji; Jinyue Chen; Yi Zhu; Junfeng Xiong; Lei Fang; Chong Liu; Jie Li; Yating Li; et al. (Water Research, 2026)

Mechanism-oriented Object–Environment–Emotion (OEE) framework for urban flood disaster assessment using multimodal social media - Yating Fan; Yuefan Li; Zhihao Shen; Da Kuang; Yu Yan (Sustainable Cities and Society, 2026)

Low-carbon and resilient innovation in traditional biomass fire-pit heating: coupling residual heat with natural ventilation to enhance nighttime thermal comfort - Wenyang Han; Chang Yi; Yating Duan; Zhixiang Zuo; Yang Yang; Mingrui Zhang; Yan Bai; Yue Xie; Yin Zhang; Kai Xie (Building and Environment, 2026)

Machine learning-based identification of basement membrane-related signature to predict recurrence and immunotherapy benefit in bladder cancer - Min Weng; Xiaojun Wang; Yating Zhan; Yangyang Guo; Zejun Yan; Liangchen Qu; Yadong Liu; Chaoyue Chen (Immunologic Research, 2026)

Heteroatom-doped MXene quantum dots: red emission tuning and dual-functional performance - Fanyong Yan; Ruixue Bai; Yating Li; Shanshan Li; Jinyun Xu; Juanru Huang; Yu Wang; Yang Fu (Analytica Chimica Acta, 2026)

Synergistic abatement of nitrogen oxides and volatile organic compounds using novel dual-functional catalysts: A critical review - Yating Li; Qiyan Zeng; Shanshan Cai; Minghui Jiang; Xingyu Jiang; Leneng Yang; Kai Yan; Paolo Centomo; Carlo Meneghini; Daiqi Ye; Yulong Shan; Peirong Chen (Journal of Environmental Sciences, 2026)

Synergistic construction of OSA-ferulic acid composite starch: Structural evolution, gel properties, and its regulation on lamb meat flavor - Meijuan Xu; Pei Yan; Xinfeng Yue; Yating Han; Xi Han; Linping Yao; Xiaojing Ma; Yuanbo Xiao; Dequan Wei; Jian Zou (Food Research International, 2026)

Building 3D conductive networks within sponge-like porous carbon nanofibers: A CNT-based cathode strategy for superior microbial fuel cells - Wei Huang; Yating He; Wenyi Yan; Longfei Qiao; Yu Tao; Xiangyu Wei; Xiumei Song; Lin Yang; Lichao Tan; Xin Wang; Zhongwei Chen (Chemical Engineering Journal, 2026)

Elucidating the degradation behavior and mechanisms of pyraquinil in soil: A comprehensive study on dissipation kinetics, transformation products and toxicity assessment - Xunyuan Jiang; Jiale Wang; Yating Zhang; Congling Huang; Yan Chen; Xuemei Tang; Peiwen Qin; Kai Wan; Hanhong Xu (Pesticide Biochemistry and Physiology, 2026)

The synergistic effect of ambient PM2.5 and psychosocial stress on cardiac health: evidence from a multi-center panel study - Yang Lan; Xianggui Li; Jian Lei; Weidong Zhang; Yunxing Jiang; Kai Wang; Lei Lei; Cuiyao Xie; Yu You; Jiaqi Zhu; Tong Wu; Jie Yan; et al. (Environmental Research, 2026)

Telomere-to-telomere genome assembly reveals the genomic architecture of disease resistance and yield coordination in elite wheat YM33 - Guofeng Lv; Yating Wang; Heping Zhang; Yuning Shen; Wenjing Hu; Datong Liu; Mengmeng Liu; Wenna Wang; Yuwen Gao; Caixia Lan; Tongde Bie; Hongya Wu; et al. (Molecular Plant, 2026)

An Enhanced Low-Power Ultrasonic Bolt Axial Stress Detection Method Using the EMD-ATWD Algorithm - Yating Liu; Chao Xu; Chunming Chen; Lianpeng Li; Yuhong Shi; Lu Yan (Journal of Marine Science and Engineering, 2026)
Traditional ultrasonic bolt stress measurement is hindered by high power consumption. Lowering excitation voltage reduces power but degrades signal-to-noise ratio (SNR), compromising accuracy. This paper proposes a synergistic algorithm combining Empirical Mode Decomposition (EMD) with Adaptive Threshold Wavelet Denoising (ATWD). The method preserves transient features by reconstructing high-frequency components via EMD, then suppresses noise by precisely processing low-frequency components using ATWD. Finally, cross-correlation estimates ultrasonic delay. Evaluated at excitation voltages from 12 V to 0.5 V, the EMD-ATWD method maintains measurement errors below 10% even at 0.5 V, improving accuracy by over 48% compared to conventional Finite Impulse Response (FIR) and Threshold Wavelet Denoising (WTD) methods, while enhancing key echo waveform fidelity by over 35%. This method provides a reliable low-power bolt stress monitoring idea for engineering applications.

Bandgap engineering of covalent two-dimensional fullerene network for near-infrared-II photothermal therapy - Rongyao Lv; Yating Wang; Xuan Wu; Xing Wang; Menghan Zhang; Xiaopeng Ma; Lifeng Yan; Wenhua Zhang; Shangfeng Yang (Chemical Engineering Journal, 2026)

Rapid evaluation of mold deterioration in maize using GC-IMS - Mengyi Liu; Yan Zhao; Yating Xiong; Zixuan Wu; Yucan Qin; Ying Xin; Haoxin Lv (Food Bioscience, 2025)

Interactions between raw dark tea chemistry and dominant fungi shape Hei brick tea quality - Yating Guo; Haijing Cui; Xinxin Wang; Haowei Guo; Xinyu Feng; Anran Yan; Yani Pan; Lixin He; Liping Liu; Kexin Zhang; Hua Fang; Hesham R. El-Seedi; et al. (International Journal of Food Microbiology, 2025)

Photosynthetic physiology and photosynthate allocation among three tuber types of chufa (Cyperus esculentus L. var. sativus Boeck) - Kaihong Bai; Yan Zhang; Yating Zhang; Xuemin Xu; Zhen Wei; Yang Lu; Shixin Zhu (Field Crops Research, 2025)

Non-alkaloidal constituents with chemotaxonomic value from Aconitum episcopale - Tianpeng Yin; Xiaojing Shen; Min Yan; Peng Yating (Biochemical Systematics and Ecology, 2025)

Protocol for Retinal Imaging and Extraction of Imaging-Derived Phenotypes from the Chinese Human Phenome Project - Lizhen Lan; Binxin Xu; Zhiqiang Yan; Yating Tang; Shengli Shen; Xuan Lan; Yidan Gao; Jianhua Jin; Yan Zheng; Chengyan Wang; Jingchun Luo; Mei Tian (Phenomics, 2025)

Community Distribution of Endophytic Bacteria in Nodules of Vicia villosa in Rocky Desertification Area of Southwest China - Yuanyuan Qi; Jinhuan Cheng; Xinyue Zhang; Li Yao; Yating He; Qiuli Yan; Jinhua Wang (Current Microbiology, 2025)

Gastrodin promotes ferroptosis in CRC cells by inhibiting SKP2 to reduce NCOA4 ubiquitination - Qiao Zhang; Zhijie Xu; Wanying Liu; Zhidong Cheng; Yating Ding; Yafeng Xie; Shengyu Yan (Tissue and Cell, 2025)

Identification of microplastics in human tear fluid and meibum: Implications for dry eye disease pathogenesis - Jingyi Wang; Huanmin Kang; Xixuan Huang; Yating Liu; Yan He; Ying Jie (Journal of Hazardous Materials, 2025)

Exploring mechanical summer pruning patterns of wine grapes in Northwest China: Effects of different canopy thickness on grape berry and wine aroma characteristics - Liang Zhang; Yating Liang; Lu Bian; Xiaoqing Tao; Yan Xu; Jinfeng Wang; Fuchun Zhang; Jiangfei Meng; Tengfei Xu (Food Research International, 2025)

Multi-omics analysis reveals the role of L-Glutamate in regulating cold tolerance of postharvest prune fruit - Yuanyuan Hou; Wanyu Yan; Rui Deng; Jiayi Wang; Yu Wang; Liang Wang; Jun Xing; Peng Jin; Yating Zhao (Postharvest Biology and Technology, 2025)

Eco-driving strategies in lane-change behaviors use: How do drivers reduce fuel consumption? - Lixin Yan; Yating Gao; Guangyang Deng; Junhua Guo (Travel Behaviour and Society, 2025)

Surface whitening prevention strategy of the mural relics from consolidation treatment: An innovative calcium protectant - Lu Wang; Zixuan Wang; Yating Wang; Guang Huang; Yalong Xing; Fuwei Yang; Zhang He; Yan Liu; Yifei Miao; Shaoxuan Niu (Chemical Engineering Journal, 2025)

Alzheimer’s Disease-Derived Outer Membrane Vesicles Exacerbate Cognitive Dysfunction, Modulate the Gut Microbiome, and Increase Neuroinflammation and Amyloid-β Production - Shouchao Wei; Xiaochen Ma; Yating Chen; Junjun Wang; Li Hu; Zhou Liu; Lang Mo; Ning Zhou; Wenrong Chen; He Zhu; Shian Yan (Molecular Neurobiology, 2025)

Water competition among coexisting plants in rock-dominated habitats of subtropical karst desertification - Lulu Cai; Kangning Xiong; Ziqi Liu; Yuan Li; Dayun Zhu; Yating Mu; Yi Chen; Rong Zhou; Xiaoyu Yan (Agriculture, Ecosystems & Environment, 2025)

Mechanism of Epigallocatechin-3-gallate in the prevention and treatment of irritable bowel syndrome: A network pharmacology and gene expression omnibus chip data-based study - Fangchen Ye; Laifu Li; Lianli Wang; Yan Ran; Lin Mei; Yating Sun; Xinping Zhang; Fei Dai (PharmaNutrition, 2025)

Combined high voltage atmospheric cold plasma and ultraviolet-cold plasma inhibited Aspergillus flavus growth and improved physicochemical properties of protein in peanuts - Luling Zhao; Jiarong Zheng; Wenjing Yan; Jing Qian; Jianhao Zhang; Jin Wang; Xiaowei Sheng; Vijaya Raghavan; Xiaohan Yang; Yuxuan Han; Taotao Cao; Yating Chen (Food Chemistry, 2025)

Characteristics of Phages and Their Interactions With Hosts in Anaerobic Reactors - Yan Zeng; Xiaozhong Zhong; Yating Chen; Min Gou; Ke Yu; Yue‐Qin Tang (Environmental Microbiology, 2025)
Anaerobic digestion (AD) of organic wastes relies on the interaction and cooperation of various microorganisms. Phages are crucial components of the microbial community in AD systems, but their diversity and interactions with the prokaryotic populations are still inadequately comprehended. In this study, 2121 viral operational taxonomic units (vOTUs) were recovered from 12 anaerobic fatty acid–fed reactors. Notably, 63.1% of these vOTUs could not be assigned to any known family, revealing a substantial presence of uncharted phages specifically associated with AD environments. Over half of the vOTUs associated with hosts had the capability to infect multiple hosts, ranging from 2 to 49, with a prevalent tendency to infect 2–5 hosts. In silico predictions of phage‐host linkages uncovered that only a small fraction of vOTUs were shared across different functional groups, including fermentative bacteria, syntrophic fatty acid–oxidising bacteria (SFOB) and methanogens. Phages linked to hosts in all three groups primarily consisted of generalists and temperate species, especially those linked to SFOB. Additionally, metabolic reconstruction identified auxiliary metabolic genes participating in fatty acid degradation, methanogenesis and energy conservation. The present study provides insights into phage characteristics and their in situ interactions with prokaryotic hosts, highlighting their ecological role in AD systems.

Polyvalent copper oxide nanozymes: Co-delivery of ROS and NO for inducing cuproptosis-like bacterial death against MRSA infections - Xufeng Zhu; Jinjun Chen; Binhua Wu; Yating Huang; Yan Zou; Chunmei Liang; Yingnian Lu; Hui Luo; Lanmei Chen; Jincan Chen (Chemical Engineering Journal, 2024)

Oxaliplatin lipidated prodrug synergistically enhances the anti-colorectal cancer effect of IL12 mRNA - Hui Liu; Yating Du; Desheng Zhan; Wenjun Yu; Yan Li; Aiping Wang; Jianpeng Yin; Haiqiang Cao; Yuanlei Fu (Drug Delivery and Translational Research, 2024)

Tide-surge interactions in Northern South China Sea: a comparative study of Barijat and Mangkhut (2018) - Yan Chen; Yating Miao; Peiwei Xie; Yuhong Zhang; Yineng Li (Frontiers in Marine Science, 2024)
In this study, the storm surge processes and characteristics of Tide-Surge Interactions (TSI) induced by the sequential tropical cyclones (TCs) BARIJAT and MANGKHUT (2018) in the Northern South China Sea (NSCS) are investigated using the numerical model. By comparing the impacts of the two TCs, we find that storm surges are significantly influenced by multiple factors. Notably, bays situated on the western side of the cyclone’s landfall point exhibit a double peak pattern in storm surge. In addition, TSI exhibits a pronounced impact across bays affected by the two TCs, with amplitude fluctuations ranging from -0.3 to 0.3 meters and contributing approximately -5% to -20% to the peaks of storm surge. Comparative analysis of TSI variations reveals that tides act as the primary determinant, significantly influencing both the magnitude and period of TSI. Dynamic analysis further highlights that variations in TSI are dominated by barotropic pressure gradient and bottom friction stress. Moreover, TSI affects the frequency of storm surges, introducing high-frequency tidal signals to storm surges and reducing the frequency of storm surges.

Risk analysis of air pollutants and types of anemia: a UK Biobank prospective cohort study - Laifu Li; Yan Ran; Yan Zhuang; Lianli Wang; Jiamiao Chen; Yating Sun; Shiwei Lu; Fangchen Ye; Lin Mei; Yu Ning; Fei Dai (International Journal of Biometeorology, 2024)

Response of fulvic acid linking to redox characteristics on methane and short-chain fatty acids in anaerobic digestion of chicken manure - Yating Chen; Zebin Tian; Yan Wang; Chuanyan Zhang; Liangzi He; Xinyu Zhao (Journal of Environmental Management, 2024)

An endophytic fungus interacts with the defensin-like protein OsCAL1 to regulate cadmium allocation in rice - Tianyu Gu; Ziai Qi; Yating Wang; Siying Chen; Jing Yan; Huapeng Qiu; Yanxuan Yu; Zijun Fang; Junmin Wang; Jiming Gong (Molecular Plant, 2024)

Constructed MXene matrix composites as sensing material and applications thereof: A review - Jinyun Xu; Yating Li; Fanyong Yan (Analytica Chimica Acta, 2024)

Zirconium and neodymium isotopes record intensive felsic volcanism in South China region during the Permian-Triassic boundary crisis - Yu Jiao; Lian Zhou; Thomas J. Algeo; Lanping Feng; Jun Shen; Yating Hu; Jinhua Liu; Yan Han; Xin Hou (Chemical Geology, 2023)

Zinc localization and speciation in rice grain under variable soil zinc deficiency - Yating Shen; Elizabeth Wiita; Athena A. Nghiem; Jingyu Liu; Ezazul Haque; Rachel N. Austin; Chheng Y. Seng; Kongkea Phan; Yan Zheng; Benjamin C. Bostick (Plant and Soil, 2023)

Dichlorodiphenyltrichloroethane inhibits soil ammonia oxidation by altering ammonia-oxidizing archaeal and bacterial communities - Jing Chen; Shuo Zhao; Yating Gan; Jing Wu; Jingcheng Dai; Hong-Jun Chao; Dazhong Yan (Environmental Pollution, 2023)

The underappreciated importance of solar radiation in constraining spring phenology of temperate ecosystems in the Northern and Eastern United States - Yating Gu; Yingyi Zhao; Zhengfei Guo; Lin Meng; Kun Zhang; Jing Wang; Calvin K.F. Lee; Jing Xie; Yantian Wang; Zhengbing Yan; He Zhang; Jin Wu (Remote Sensing of Environment, 2023)

Atmospheric ammonia in China: Long-term spatiotemporal variation, urban-rural gradient, and influencing factors - Jinyan Dong; Baojie Li; Yan Li; Rui Zhou; Cong Gan; Yongqi Zhao; Rui Liu; Yating Yang; Teng Wang; Hong Liao (Science of The Total Environment, 2023)

Insights into autotrophic carbon fixation strategies through metagonomics in the sediments of seagrass beds - Xiangqun Chi; Zhiyi Zhao; Qiuxia Han; Huaxiao Yan; Bei Ji; Yating Chai; Shengying Li; Kun Liu (Marine Environmental Research, 2023)

Alpine-style tectonic nappe stacking in an Archean suture zone: Quantitative structural profile places constraints on orogenic architecture - Yating Zhong; Timothy M. Kusky; Lu Wang; Chuanhai Wang; Yaying Peng; Tingting Wang; Chao Yan (Gondwana Research, 2023)

Single-cell-resolution transcriptome map revealed novel genes involved in testicular germ cell progression and somatic cells specification in Chinese tongue sole with sex reversal - Hong-Yan Wang; Xiang Liu; Jian-Yang Chen; Yingyi Huang; Yifang Lu; Fujian Tan; Qun Liu; Mingming Yang; Shuo Li; Xianghui Zhang; Yating Qin; Wenxiu Ma; et al. (Science China Life Sciences, 2023)

Remediation of heavy-metal-contaminated soil with two organic acids: Washing efficiency, recovery performance, and benefit analysis - Zilin He; Lulu Long; Han Yuan; Han Pang; Yating Wang; Liang Ye; Min Xu; Chao Chen; Yan Liu; Yinlong Xiao; Changlian Xu; Jun Wu; et al. (Journal of Cleaner Production, 2023)

Deviations of satellite-measured sea surface salinity caused by environmental factors and their regional dependence - Yating Ouyang; Yuhong Zhang; Jianwei Chi; Qiwei Sun; Yan Du (Remote Sensing of Environment, 2023)

Hippocampal Iron Accumulation Impairs Synapses and Memory via Suppressing Furin Expression and Downregulating BDNF Maturation - Yating Zhang; Xue Bai; Yi Zhang; Shanshan Yao; Yiduo Cui; Lin-Hao You; Peng Yu; Yan-Zhong Chang; Guofen Gao (Molecular Neurobiology, 2022)

Microfossil analysis of dental calculus and isotopic measurements reveal the complexity of human-plant dietary relationships in Late Bronze Age Yunnan - Tingting Wang; Dong Wei; Zhilong Jiang; Xiumin Xia; Yan Wu; Zhen Han; Yating Qu; Yaowu Hu; Benjamin T. Fuller (Archaeological and Anthropological Sciences, 2022)

Pore-scale study on the characteristic hydraulic conductivity of a dispersive lean clay affected by salinity and freeze–thaw - Yan Han; Qing Wang; Jing Liu; Weitong Xia; Jiaqi Wang; Jiejie Shen; Yating Chen (Bulletin of Engineering Geology and the Environment, 2022)

Regional difference of sea surface salinity variations in the western tropical pacific - Yating Ouyang; Yuhong Zhang; Jianwei Chi; Qiwei Sun; Yan Du (Journal of Oceanography, 2021)
Regional difference of sea surface salinity (SSS) variations in the western tropical Pacific is investigated with Ocean Reanalysis System 5 datasets. Three robust zonal bands of SSS variations have been identified in the northwestern tropical Pacific (NWTP), the western equatorial tropical Pacific (WEqP), and the southwestern tropical Pacific (SWTP), respectively. SSS in the WEqP and the SWTP has a strong interannual variability that is related to ENSO. In the WEqP, SSS variations are mainly controlled by anomalous freshwater flux, while in the SWTP they are governed by both freshwater forcing and oceanic processes. In the NWTP, SSS variations present a low-frequency variability that is correlated with Interdecadal Pacific Oscillation (IPO), which is mostly dominated by the freshwater flux and strongly adjusted by the ocean advection and mixed layer changes. After removing interannual signals, the SSS in all three regions are highly related to IPO, indicating that IPO has a general influence on the western tropical Pacific.

Concentration of circulating microparticles: a new biomarker of acute heart failure after cardiac surgery with cardiopulmonary bypass - Yuquan Li; Haoxiang Yuan; Caiyun Chen; Chao Chen; Jian Ma; Yating Chen; Yan Li; Yupeng Jian; Donghong Liu; Zhijun Ou; Jingsong Ou (Science China Life Sciences, 2021)

Ephedrannin B exerts anti-viral and anti-inflammatory properties in BEAS-2B cells infected with respiratory syncytial virus - Shu Hou; Xiaoyan Xu; Yating Wang; Yan Yang (Journal of Biosciences, 2020)

Inhalation cancer risk estimation of source-specific personal exposure for particulate matter–bound polycyclic aromatic hydrocarbons based on positive matrix factorization - Bin Han; Yan You; Yating Liu; Jia Xu; Jian Zhou; Jiefeng Zhang; Can Niu; Nan Zhang; Fei He; Xiao Ding; Zhipeng Bai (Environmental Science and Pollution Research, 2019)

The response of relative humidity to centennial-scale warming over the southeastern Tibetan Plateau inferred from tree-ring width chronologies - Chunming Shi; Valérie Daux; Zongshan Li; Xiuchen Wu; Tianyi Fan; Qian Ma; Xiaoxu Wu; Huaiyu Tian; Matthieu Carré; Duoying Ji; Wenli Wang; Annette Rinke; et al. (Climate Dynamics, 2018)

Assessing the inhalation cancer risk of particulate matter bound polycyclic aromatic hydrocarbons (PAHs) for the elderly in a retirement community of a mega city in North China - Bin Han; Yating Liu; Yan You; Jia Xu; Jian Zhou; Jiefeng Zhang; Can Niu; Nan Zhang; Fei He; Xiao Ding; Zhipeng Bai (Environmental Science and Pollution Research, 2016)

Network analysis of eight industrial symbiosis systems - Yan Zhang; Hongmei Zheng; Han Shi; Xiangyi Yu; Gengyuan Liu; Meirong Su; Yating Li; Yingying Chai (Frontiers of Earth Science, 2016)

Regional environmental risk assessment for the Nanjing Chemical Industry Park: an analysis based on information-diffusion theory - Xiaojie Meng; Yan Zhang; Xiangyi Yu; Junhong Bai; Yingying Chai; Yating Li (Stochastic Environmental Research and Risk Assessment, 2014)

Analysis of urban metabolic processes based on input-output method: model development and a case study for Beijing - Yan Zhang; Hong Liu; Bin Chen; Hongmei Zheng; Yating Li (Frontiers of Earth Science, 2014)

Sociality and oxytocin and vasopressin in the brain of male and female dominant and subordinate mandarin voles - Xufeng Qiao; Yating Yan; Ruiyong Wu; Fadao Tai; Ping Hao; Yan Cao; Jianli Wang (Journal of Comparative Physiology A, 2014)

Effect of culture temperature on TNFR-Fc productivity in recombinant glutamine synthetase-chinese hamster ovary cells - Li Fan; Liang Zhao; Zhaoyang Ye; Yating Sun; Tianci Kou; Yan Zhou; Wen-Song Tan (Biotechnology Letters, 2010)